Increased Tax Avoidance By Leverage Through Corporate Social Responsibility Disclosure - Pattiasina, Victor; Rina Sejati, Fajar; Yamin Noch, Muhamad; Aldrin Akbar, Muhamad; Prasetyaningrum, Septyana; Nugrohowati, Nur Fitriani; Yohannis Tamaela, Eduard (E-Jurnal Akuntansi, 2021)
This study aims at examining and analysing the effect of leverage on tax avoidance. The moderating variable is disclosing corporate social responsibility. The population in the current study is manufacturing companies in the consumer goods industry sector. The companies were listed on the Indonesia Stock Exchange (ISE) from 2013 to 2017. To examine the hypotheses, Moderation Regression Analysis (MRA) was applied. The results prove that leverage has a positive and significant effect on tax avoidance. Moreover, the corporate social responsibility disclosure is proven to strengthen the effect of leverage on tax avoidance. Keywords: Leverage; Tax Avoidance; Corporate Social Responsibility.